Unilever Vietnam: A one-rinse revolution towards a sustainable future (B) - REDDY, Srinivas (Institutional Knowledge at Singapore Management University, 2014)
Part B of this case series takes place in December 2008, a little more than a year following the events of part A. Although significant progress has been made since then, the Comfort One Rinse range has not yet reached 50% market penetration… though neither has Downy. The biggest obstacle is rural activation. What more can Nguyen do to push into the rural market? In the second part of this case series, students will recognise potential roadblocks to consumer adoption of new, innovative products and formulate strategies to overcome such roadblocks.